2016
DOI: 10.1038/ncomms10529
|View full text |Cite
|
Sign up to set email alerts
|

RAG2 and XLF/Cernunnos interplay reveals a novel role for the RAG complex in DNA repair

Abstract: XRCC4-like factor (XLF) functions in classical non-homologous end-joining (cNHEJ) but is dispensable for the repair of DNA double-strand breaks (DSBs) generated during V(D)J recombination. A long-standing hypothesis proposes that, in addition to its canonical nuclease activity, the RAG1/2 proteins participate in the DNA repair phase of V(D)J recombination. Here we show that in the context of RAG2 lacking the C-terminus domain (Rag2c/c mice), XLF deficiency leads to a profound lymphopenia associated with a seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
133
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(142 citation statements)
references
References 70 publications
8
133
1
Order By: Relevance
“…The difference in effect on DNA repair and V(D)J recombination in XLF deficiency might be explained by the 2-tier synapse model that has recently been proposed by Lescale et al, showing that both the RAG-PCC and XLF ensure stabilization of DNA ends after RAG1/2 cleavage. 24 They showed that the RAG-PCC has functional redundancy with XLF in RAG DSB stabilization, which indicates that in the presence of RAG, DNA end repair can be achieved during V(D)J recombination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in effect on DNA repair and V(D)J recombination in XLF deficiency might be explained by the 2-tier synapse model that has recently been proposed by Lescale et al, showing that both the RAG-PCC and XLF ensure stabilization of DNA ends after RAG1/2 cleavage. 24 They showed that the RAG-PCC has functional redundancy with XLF in RAG DSB stabilization, which indicates that in the presence of RAG, DNA end repair can be achieved during V(D)J recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery in 2005, several functions have been described for XLF. It stimulates LIG4 activity, 21,22 and it can form long filaments with XRCC4 that keep the DNA ends together in a ligation synapse, 24,[48][49][50][51] and XLF is essential for gap-filling by polymerase (pol) l and polm during NHEJ. The latter function is interesting, as poll and polm belong to the same polX family of polymerases as For personal use only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To help explain these findings, functional redundancy with other factors was suggested and, in due course, demonstrated by XLF loss being shown to display nonepistatic or synthetic-lethal relationships with loss of components of the ATM-H2AX-53BP1 pathway or with C-terminal mutants of the V(D)J recombinase protein RAG2 (Zha et al 2011;Liu et al 2012;Oksenych et al 2012;Lescale et al 2016a). Our data reveal that PAXX and XLF also share Synthetic lethality between PAXX and XLF one or more redundant functions, as, unlike single mutants, mice lacking both proteins display severe growth defects, extensive cell death in the CNS, and an almost complete block to lymphocyte development similar to that of Xrcc4 −/− or Lig4 −/− mice.…”
Section: Xlfmentioning
confidence: 99%
“…Potential processes in which XLF and DSBR factors may be functionally redundant are not well-characterized but may include tethering ends or facilitating their joining (6,16). Notably, XLF also has functional redundancy with a truncation mutant of RAG2 for CE joining during V(D)J recombination, potentially implicating the RAG2 protein in some aspect of shepherding the V(D)J recombination joining reaction specifically to C-NHEJ (20,21).…”
mentioning
confidence: 99%